Pemanfaatan Teknologi Informasi dan Komunikasi dalam Administrasi Pengarsipan di Surabaya - Rio Febriannur Rachman (Idarotuna : Journal of Administrative Science, 2023)
Policies based on information and communication technology are unavoidable in the age of new media. One of the first governments to apply electronic and internet-based regulations was the Surabaya City Government. This article discusses the e-Archives initiative, a policy implemented by the Surabaya Library and Archives Service in 2017 and one of its policies. In an effort to administer archives policies within the Surabaya City Government, the implementation of the e-Archives policy is being described in this study. Technology determination and public policy analysis serve as the guiding theories. Additionally, a number of ideas, including Maqashid Syariah and sustainable development objectives, form the basis for discussion. The methodology utilized in this study is qualitative with a literature study approach, in which the literary sources serve as the main source of information. According to the study's findings, e-Archive policies adhere to the principles of information and communication technology use. E-Archives are a flexible way to carry out government directives.This initiative is in line with Maqasid Syariah Al-Ammah's tenets and the objectives of sustainable development, particularly given its ambition to build environmentally responsible cities and communities that can adapt to the difficulties of the modern world. This page is intended to contribute to the body of knowledge on technology-based public policy and how it aligns with Islamic ideals.